Performance of Pervious Concrete Containing Kenaf (Hibiscus cannabinus L.) Fibres - Fung-Lung, Chang; Wen-Pei, Low; Meng-Jie, Teo; Hong-Aik, Lauw (INTI International University, 2018)
The present study investigates the feasibility of adding kenaf fibres (Hibiscus cannabinus L.) in pervious concrete. Pervious concrete is a special concrete designed to possess large quantity of voids for water permeability. Kenaf fibres is selected to be added into the concrete mixture due to the exceptional engineering properties apart from being locally available. The fibres is added at 0%, 0.1% and 0.3% by weight of cement to produce three different batches of concrete mixtures. The density, porosity, constant head water permeability and compressive strength were investigated. Experimental results showed that the permeability is directly proportional to the porosity of the concrete specimens. Maximum porosity of 40% is recorded, corresponds to the maximum water permeability of 6.3L/min. Addition of kenaf fibres at an increasing quantity however caused agglomeration of cement paste, kenaf fibres and the aggregate particles that affect the voids distribution and the compressive strength. Nonetheless, the concrete continue to show steady increment in compressive strength with respect to the testing age where highest strength of 6.8MPa is observed for control mix, followed by 5.8MPa and 4.7MPa, respectively for concrete of 0.1% and 0.3% fibres addition. Considering water permeability as the key feature of pervious concrete, addition of kenaf fibres in the concrete is feasible and could be applied at locations where excessive loadings are unlikely. Therefore, the study can be further extended to reduce the high voids content whilst increasing the compressive strength.